2018
DOI: 10.3389/fneur.2018.00279
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in Parkinson’s Disease Is Associated With Alterations in Affective and Sensorimotor Striatal Networks

Abstract: A subset of patients with Parkinson’s disease (PD) experiences problems with impulse control, characterized by a loss of voluntary control over impulses, drives, or temptations regarding excessive hedonic behavior. The present study aimed to better understand the neural basis of such impulse control disorders (ICDs) in PD. We collected resting-state functional connectivity and structural MRI data from 21 PD patients with ICDs and 30 patients without such disorders. To assess impulsivity, all patients completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 54 publications
3
29
1
2
Order By: Relevance
“…These results are consistent with previous studies that define changes to delayed discounting, and altered reward strategies, in patients with ICBs 6,15,27,29,58 . Interestingly, we observed significant differences between the ICB+ and ICB‐ groups in only one first‐order factor (attention) and in the second order factor non‐planning (self‐control and cognitive complexity).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous studies that define changes to delayed discounting, and altered reward strategies, in patients with ICBs 6,15,27,29,58 . Interestingly, we observed significant differences between the ICB+ and ICB‐ groups in only one first‐order factor (attention) and in the second order factor non‐planning (self‐control and cognitive complexity).…”
Section: Discussionsupporting
confidence: 93%
“…1). Although many studies of PD report BIS‐11 total scores, and some of which report second‐order scores, 6,15,27‐29 none to our knowledge have investigated first‐order factors. Although these studies do tend to find differences in total and second‐order level BIS‐11 scores, there are inconsistencies on how second‐order factors differ between PD and healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there is a paucity – and inconsistency – of studies that examined reflection impulsivity in PD patients. For example, when comparing PD+ICD with PD‐ICD patients on the Beads Task (Furl & Averbeck, ), one study showed that the former group had more reflection impulsivity than the latter (Djamshidian et al ., ), whereas another study did not find a significant between‐group difference on the number of drawn beads before making a decision (Ruitenberg et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The neural bases of these 'non-normalising' DA effects, while incompletely characterised, are thought to involve the dopamine-rich ventral striatum and connected regions of the mesolimbic pathway (Riba et al 2008;Weintraub et al 2010;Voon et al 2011;Ye et al 2011). Such regions comprise large-scale, cortico-striato-thalamic circuitry implicated in higher-order cognitive processes supported by dopamine, relevant for impulsivity and disturbed in PD (Honey et al 2003;Everitt and Robbins, 2005;Dagher and Robbins, 2009;Hacker et al 2012;Agosta et al 2014;Ruitenberg et al 2018). However, susceptibility to non-normalising DA effects varies across individuals, ostensibly in line with neurochemical and cognitive phenotypes (e.g., Dagher and Robbins, 2009;Buckholtz et al 2010;Housden et al 2010;O'Sullivan et al 2011;Vargas and Cardoso, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent functional magnetic resonance imaging (FMRI) research, employing analysis methods sensitive to the synchronicity of activity, or 'functional connectivity', within largescale brain networks, has suggested that sources of clinical-pharmacological variability may be explained by systems-level variability measurable in cortico-subcortical signalling patterns relevant for both dopamine function (e.g., in healthy subjects: Nagano-Saito et al Cole et al 2012; and dysfunction in PD (Kwak et al 2010;Hacker et al 2012;Helmich et al 2012;Ruitenberg et al 2018). For example, previously we have demonstrated evidence of specific, large-scale, higher-order neural systems possessing task-independent functionality relevant for dopaminergic modulations, as measured by 'resting-state' network (RSN) functional connectivity .…”
Section: Introductionmentioning
confidence: 99%